STUDENT LEARNING ACTIVITY ANALYSIS ON BUILDING SPACE MATERIALS - Aam Amaliyah; Gilang Ramadhan; Lois Mustafa; Tiara Nur Cahyani (PROGRES PENDIDIKAN, 2022)
This study aims to analyze the activities of teachers, students' activities in mathematics learning outcomes in the material for building space for high-class students, especially for elementary school education. The subjects of this research are fifth grade students at SDN Kutabumi 1, which is a school located in one of the areas in Tangerang Regency, precisely in Kutabumi Village for the 2021-2022 academic year with a total of 24 students. The results showed that teacher activity increased with very good criteria and student activity with very active criteria. It can be concluded that the teacher's activities run smoothly, student activities and learning outcomes of Mathematics in Building Spaces material increase at each meeting. This research is a type of quantitative descriptive research. This study uses a problem-solving ability test sheet and student activity observation sheets as research instruments. Because each level requires a different absorption of learning, the higher the level of majority education, the more power needs to be spent to achieve something that is expected. This research uses the interview method to one of the teachers at SDN Kutabumi 1. The interviews were conducted directly/Offline by approaching the resource persons. Hopefully, after this research and interview, we and the team will get answers and solutions to the problem solving that we are researching and make learning which is much better than before this research and research was conducted.